KARAKTERISTIK ASHABUL A`RAF PERSPEKTIF TAFSIR IBNU KATSIR - Asmuni - Falahul (el-'Umdah, 2021)
This article titled characteristics of Ashabul A`raf In perspective of Ibn Kathir's Interpretation. There is a boundary between heaven and hell where the boundary is named after al-A`raf. Allah SWT. also mentioned that there was a group of people who were in the A`raf. Those in Araf are also called Ashabul Araf. The discussion of this problem will be described using research in the form of library research, therefore the data used is qualitative data. The method used is the thematic method or maudhu`i. In the interpretation of classical and contemporary scholars, although there are some opinions of the commentators there is a difference, however, the majority of opinions have the same interpretation that is close to each other with Ibn Kathir's interpretation, namely the inhabitants of A'raf are people whose good and bad are the same. The characteristics of Ashabul A`raf in al-Qur`an according to the interpretation of the cleric of Imam Ibn Kathir's classical interpretation namely Ashabul A`raf can see the conditions of the inhabitants of heaven and the inhabitants of hell, can know the signs of the inhabitants of heaven and hell, have a great desire to be able enter heaven, the A'raf inhabitants have a sense of worry, anxiety and fear if they are included with the inhabitants of hell, the inhabitants of A`raf can dialogue with the inhabitants of hell and heaven, they can give a call or reproach to the residents of hell they know . Ashabul A`raf is the last group to be put into heaven.